2011
DOI: 10.1097/aog.0b013e31822e5c02
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Double Vaccination With the 2009 Pandemic Influenza A (H1N1) Vaccine During Pregnancy

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 24 publications
3
40
0
Order By: Relevance
“…Before vaccination, a cross-reactive antibody to the 2009 H1N1 influenza virus was detected in 6-9% of people aged 18-64 years and 33% of those aged >60 years. In our study [9], the pre-vaccination antibody positivity rate among 124 pregnant women demonstrated a similar rate (7.2%). For the novel influenza A (H1N1) virus, few women of childbearing age had pre-existing antibodies and the initial vaccine formulation available was monovalent, in contrast to the trivalent seasonal vaccines.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Before vaccination, a cross-reactive antibody to the 2009 H1N1 influenza virus was detected in 6-9% of people aged 18-64 years and 33% of those aged >60 years. In our study [9], the pre-vaccination antibody positivity rate among 124 pregnant women demonstrated a similar rate (7.2%). For the novel influenza A (H1N1) virus, few women of childbearing age had pre-existing antibodies and the initial vaccine formulation available was monovalent, in contrast to the trivalent seasonal vaccines.…”
Section: Discussionsupporting
confidence: 78%
“…A single dose of monovalent vaccine against 2009 H1N1 influenza virus showed a favorable immune response in pregnant women [9,10]. The efficiency of vaccination during pregnancy was not influenced by maternal immunological status or by the gestational stage when the vaccine was received [9].…”
Section: Discussionmentioning
confidence: 99%
“…Across strains, 95–100% of infants achieved a titer of 1:40 while 50–93% achieved a titer of 1:110. These comparatively high titer values in cord blood versus maternal serum reflect active transport mechanisms; cord blood antibodies including influenza-specific IgG typically considerably exceed maternal levels [35–37], as observed in the current study. However, there are a number of factors that can impede transfer of antibody, and thus higher titers in neonates versus mothers is not observed in all studies [9].…”
Section: Commentmentioning
confidence: 63%
“…Accordingly, three comparisons were made: 2nd‐trimester vaccination compared with 1st‐trimester vaccination, the 3rd trimester compared with the 2nd and the 3rd trimester compared with the 1st. For studies that included a two‐dose vaccine group, these data were analysed in separate meta‐analyses (trimester of vaccination defined by the timing of the first dose) . Seven primary meta‐analyses (Figure & Figures , , , ) were conducted, plus four separate meta‐analyses of results after a second dose (Figures , , , ).…”
Section: Methodsmentioning
confidence: 99%